Flourishing Among Emerging Adulthood: A Perspective From Anchor Personality - Alifah Nur Istiqomah; Bagus Riyono (Changing Societies & Personalities, 2024)
The purpose of well-being theory in positive psychology is to help people achieve flourishing conditions. Personality is an essential factor influencing flourishing, but no research has examined the relationship between anchor personality and flourishing. Anchor is something that is trusted as a mainstay in solving problems. With that in mind, this study aimed to determine the relationship between anchor virtues, materials, self, and others on flourishing among emerging adulthood. This current research used a non-experimental quantitative method by online survey. The research participants are Indonesian citizens aged 18–25 years. The results showed that virtue was the only anchor that predicted overall flourishing positively and significantly. Anchor virtues also significantly predicted each flourishing elements separately. Anchor self and materials did not predict flourishing significantly, while anchor others predicted flourishing negatively. This study empirically proves the importance of emerging adulthood in adhering to virtues to achieve a flourishing condition. When an individual places virtues as the main anchor, they hold on to an anchor with high abstraction power, not limited by space and time and universal; so that stability and positively impact well-being can be achieved.